“FIDZ-ABCT” MODEL TO IMPROVE CROSS INFECTION PREVENTION ON TOOTH EXTRACTION - Fidzah Nurfajrina Murad; Diyah Fatmasari; Tri Wiyatini (Politeknik Kesehatan Kemenkes RI Jakarta I, 2023)
Background: The profession of dental and oral therapist (TGM) has a high risk of disease transmission, so it is important to prevent cross-infection in dental extraction services because they come into direct contact with the patient's body fluids. The description of TGM behavior in Maros Regency in preventing cross infection is not optimal, 50% do not carry out SOPs properly, 63% do not maintain hand hygiene, 50% do not change handscoons and sterile masks every time they change patients. Efforts are needed to increase cross-infection prevention behavior with the